Stores separation simulation development: a roadmap to system realisation via intelligent data management system - Faat, Shamsul Bahri; Md Zhahir, Md Amzari; Ahmad, Mohamed Tarmizi; Mohd Ajir, Mohd Ramly (Trans Tech Publications, 2014)
An Intelligent-Data Management System (IDMS) for store separation analysis has been developed for Stores Separation Simulation program. The characteristics of the IDMS generically focuses on gathering, collecting, analysing, reporting, summarising and visualising validated data prior separation activity in simulated environment. The components of IDMS are Aircraft Configuration, Interface Configuration, Stores Geometry, Pylon Configuration and Cube (a multi-dimensional visibility of Form, Fit and Function stores-platform Data Verifier). Overall, this project combined information from separation patterns analysis by integrating multi-dimensional databases, systematic-data orchestration; rules based data mining for stores separation verifier into one data management system. This paper presents the program review of overall store separation simulation program.